Validation of novel patient-centred juvenile idiopathic arthritis-specific patient-reported outcome and experience measures (PROMs/PREMs) - Laura E. Lunt; Stephanie Shoop-Worrall; Nicola Smith; Gavin Cleary; Janet McDonagh; Andrew D. Smith; Wendy Thomson; Flora McErlane (BMC, 2020)
Abstract Background Measuring the outcomes that matter to children and young people (CYP) with juvenile idiopathic arthritis (JIA), is a necessary precursor to patient-centred improvements in quality of clinical care. We present a two-centre validation of novel JIA patient-reported outcome and experience measures (PROM and PREM) developed as part of the CAPTURE-JIA project. Methods CYP with JIA were recruited from paediatric rheumatology clinics, completing the CAPTURE-JIA PROM and PREM, CHAQ and CHU 9D. A subset participated in face-to-face interviews and completed the PROM/PREM 1 week later. The OMERACT filter was applied and the three domains of validation assessed. Truth assessments included cognitive interviewing, sensitivity analysis and Spearman's correlations. Discrimination assessments included specificity and reliability testing. Feasibility was assessed using time to form completion and proportion of missing data. Results Eighty-two CYP and their families were recruited; ten cognitive interviews and fifteen PROM/PREM test/retests were conducted. Truth: CYP and parents understood the PROM/PREM and felt important areas were covered. PROM criteria had high sensitivities (> 70%) against similar items on the CHU 9D, with the exception of fatigue (58%). Correlations between similar PROM and CHU 9D criteria were moderate to very strong (coefficients 0.40-0.82.) Discrimination: high specificities (> 70%) on corresponding PROM and CHU 9D domains. Feasibility: median completion times for PROM 60 s (IQR 38-75) and PREM 49 s (IQR 30-60) respectively. Conclusion The CAPTURE-JIA PROM and PREM are valid and feasible in UK paediatric rheumatology clinics. Embedding routine collection into clinical care would be a major step towards improving quality of care.